Screen and Verification for Transgene Integration Sites in Pigs - Linyuan Ma (Nature Portfolio, 2018)
Abstract Efficient transgene expression in recipient cells constitutes the primary step in gene therapy. However, random integration in host genome comprises too many uncertainties. Our study presents a strategy combining bioinformatics and functional verification to find transgene integration sites in pig genome. Using an in silico approach, we screen out two candidate sites, namely, Pifs302 and Pifs501, located in actively transcribed intergenic regions with low nucleosome formation potential and without potential non-coding RNAs. After CRISPR/Cas9-mediated site-specific integration on Pifs501, we detected high EGFP expression in different pig cell types and ubiquitous EGFP expression in diverse tissues of transgenic pigs without adversely affecting 600 kb neighboring gene expression. Promoters integrated on Pifs501 exhibit hypomethylated modification, which suggest a permissive epigenetic status of this locus. We establish a versatile master cell line on Pifs501, which allows us to achieve site-specific exchange of EGFP to Follistatin with Cre/loxP system conveniently. Through in vitro and in vivo functional assays, we demonstrate the effectiveness of this screening method, and take Pifs501 as a potential site for transgene insertion in pigs. We anticipate that Pifs501 will have useful applications in pig genome engineering, though the identification of genomic safe harbor should over long-term various functional studies.